La enseñanza virtual en el desarrollo del lenguaje en tiempos de Covid en el subnivel de Educación Inicial ii en la Unidad Educativa Fiscal Municipio de Loreto en la parroquia Loreto, cantón Loreto, provincia Orellana en el año lectivo 2020 - 2021. - Andi Shiguango, Cleria Alexandra (2021)
This educational intervention work highlights the importance of virtual education in times of COVID due to the need to continue with the training and development of the language mainly, because I can achieve goals in training in the future, allowing the continuation of the school year virtually, because techniques that apply technology to achieve communication skills that allow you to interact with your peers and be participatory in social and personal life. Theoretically, support the variables in the study, as necessary, with the necessary knowledge to intervene in order to solve a critical need and also solve the possible problem that will help us to elaborate this project. Language is a form of communication that the child does not need to be able to express his emotions, feelings, ideas, concerns and discomfort in all possible ways to understand other people with empathy and share experiences that will last in time and space. Virtual education but being an innovative experience is the best way for digital natives to become familiar with technology and men as part of their lives. Virtual education could not meet the needs of the protagonist of education (the child) to focus on secondary aspects. With the health emergency of COVID 19, there have been some gaps in the use of technology that has given teachers and students the grace of virtual education, and the fear of being ignored in the approach of virtual tools that they have managed to develop the language of children. adequately involve family priests in the learning process. Keywords: education, virtual, language development.